Reshaping research in crisis: bibliometric analysis of Ecuadorian public universities during COVID-19 (2019–2021) - Bill Serrano-Orellana; Jorge Guido Sotomayor-Pereira; Oscar Geovanny Riofrio Orozco; Luis Brito-Gaona; Patricio Alvarez-Muñoz; Patricio Alvarez-Muñoz; Marco Faytong-Haro (Frontiers in Education, 2025)
IntroductionEcuadorian public universities have significantly expanded their scientific output in recent years; however, few studies have conducted a multivariate bibliometric analysis to assess how these institutions adapted their research agendas during the COVID-19 pandemic.MethodsThis study examines publication patterns from 2019 to 2021 using data from the Web of Science, focusing on four primary research areas: Education, Social Sciences, Engineering, and Multidisciplinary Sciences. Institutional performance was evaluated across seven variables: article count, citation impact, and open-access prevalence. By applying a dynamic HJ-Biplot approach in R (dynBiplotGUI), we visualized the relationships among the 24 public universities and tracked their temporal evolution.ResultsThe results indicated that Education and Social Sciences were the most productive areas, with the Technical University of Machala leading in both publication volume and number of citations. Open-access publishing exhibited substantial growth—reaching up to 300% in some institutions—and was positively linked to higher citation impact. The dynamic trajectories revealed a noticeable shift among mid-tier institutions toward engineering research and open dissemination models.DiscussionThese findings underscore the adaptability of Ecuadorian universities during global disruptions, emphasizing the importance of multivariate bibliometric approaches for strategic research planning, policymaking, and the promotion of open science in emerging contexts.